Throughput maximization of a UAV-Enabled Two-Way Relaying System - Guo, Xianzhen; Li, Bin; Cong, Jiayi; Zhang, Ruonan (IEEE International Conference on Communications (2003), 2021)
In this paper, we consider a UAV-enabled two-way relaying system where the UAV relay assists the information exchange between two ground users (GUs). The two-slot physical network coding scheme (PNC) for information exchange is adopted. The rate region of this scheme in this UAV-enabled relaying system is firstly analyzed. Then, we maximize the system average sum rate under this scheme by jointly optimizing the time resources allocation, transmission powers of the transceivers, and the UAV trajectory subject to the UAV mobility constraints and the information causality constraints. The formulated problem is a nonconvex optimization problem which is hard to solve directly. We propose an iterative algorithm by applying the successive convex approximation and block coordinate descent techniques to solve this problem. Specifically, the time resources allocation, transmission powers and the UAV trajectory are alternatively optimized in each iteration. In addition, the non-convex trajectory optimization problem is solved by successively solving an approximate convex optimization problem. To gain more insights, we also investigate the effects of traffic pattern, which is defined as the ratio between the traffic in two directions, on the system performance by considering a new traffic pattern constraint. Numerical results show that the proposed relaying scheme with moving relay can achieve great throughput gains as compared to the conventional scheme with static relay.